Recent scattering approaches to structure and dynamics of polymer nanocomposites - Kruteva, M.; Genix, A.-C.; Holderer, O.; Oberdisse, J. (Frontiers in Soft Matter, 2022)
The characterization of polymer nanocomposites on molecular length- and timescales is a challenging task, which is indispensable also for the understanding of macroscopic materials properties. Neutron scattering is one of the techniques which are very well suited for studying structure and molecular motion in such soft matter systems. X-rays can also be used for the same purpose, with however a higher energy and thus a different focus in dynamics, where they are better suited for nanoparticle motion. In this mini-review, we aim at highlighting recent results in the field of polymer nanocomposites, including nanoparticle structure in various experimental systems, from model to industrial, and polymer and particle dynamics. This allows establishing the link between microscopic properties and macroscopic ones, in particular rheology.